Lung ultrasound score as a predictor of ventilator use in preterm infants with dyspnea within 24 h after dhospitalization - Lihua Zhang; Jinnan Feng; Di Jin; Zekun Yu; Yangming Qu; Meiyu Zheng; Hui Wu (Pediatrics and Neonatology)
Background: Selecting the correct ventilation strategy is crucial for the survival of preterm infants with dyspnea in NICU. Lung ultrasound score (LUSsc) is a potential predictor for respiratory support patterns in preterm infants. Methods: We prospectively included 857 preterm infants. LUS was performed in the first 2 h after admission, and LUSsc was determined by two specialist sonographers. Participants were divided into two categories according to gestational age (<32+0 weeks and 32+0–36+6 weeks) and randomly divided into a training set and a validation set. There were two main outcomes: invasive and non-invasive respiratory support. In the training set, clinical factors were analyzed to find the best cut-off value of LUSsc, and consistency was verified in the verification set. The choice of invasive respiratory support was based on neonatal mechanical ventilation strategies. Results: Preterm infants with invasive respiratory support had a higher LUSsc, greater use of Pulmonary Surfactant（PS）, and lower Oxygenation Index（OI）、birth weight than those with non-invasive support. In the <32+0 weeks group, the area under the curve (AUC) for the receiver operating characteristic curve plotted with 2-h LUSsc was 0.749 (95% CI: 0.689–0.809), the cut-off point of LUSsc was 8, and the sensitivity and specificity were 74.0% and 68.3%, respectively. In the 32+0–36+6 weeks group, the AUC was 0.863 (95% CI: 0.811–0.911), with a cut-off point of 7. Sensitivity and specificity were 75.3% and 0.836%, respectively. In the validation set, using the actual clinical respiratory support selection results for verification, the validation results showed for the <32+0 weeks group (Kappa value 0.660, P < 0.05, McNemar test P > 0.05) for preterm 32+0–36+6 weeks (Kappa value 0.779, P < 0.05, McNemar test P > 0.05). Conclusion: The LUSsc showed good reliability in predicting respiratory support mode for preterm infants with dyspnea.Registered at ClinicalTrials.gov (identifier: chiCTR1900023869).